Development of EST-SSRs based on the transcriptome of Castanopsis carlesii and cross-species transferability in other Castanopsis species. - Xiaoru Zhong; Mengyang Xu; Ting Li; Rongxi Sun (PLoS ONE, 2023)
Castanopsis carlesii (Hemsl.) Hay. is a widely distributed and dominant tree species native to subtropical China with significant ecological and economic value. Due to serious human-related disturbance, its wild resources have been increasingly reduced, and whether may result in the loss of genetic diversity. However, no population genetics studies of natural C. carlesii have been reported to date. Microsatellite markers have been a useful tool in population genetics. Therefore, we developed EST-SSR markers based on the transcriptome sequencing of C. carlesii leaves. A total of 149,380,224 clean reads were obtained, and 63,012 nonredundant unigenes with a mean length of 1,034 bp were assembled and annotated based on sequence similarity searches in the Nr, Nt, KO, SwissProt, PFAM, KOG, and GO databases. The results showed that only 5,559 (8.82%) unigenes were annotated in all seven databases, but 46,338 (73.53%) could be annotated in at least one database. A total of 31,459 potential EST-SSRs were identified in 18,690 unigenes, with an average frequency of one SSR approximately 2 kb. Among the 100 EST-SSR primer pairs designed, 49 primer pairs successfully produced the expected product by amplification, with a success rate of 49%, but only 20 primer pairs showed abundant polymorphisms. Polymorphisms were verified using 25 samples from C. carlesii in Qimen, Anhui. A total of 119 alleles were detected, with a mean number of alleles (Na) of 5.95 per locus and a mean polymorphism information content (PIC) of 0.6125. All the 20 newly developed EST-SSR markers were verified in other Castanopsis species (C. sclerophylla, C. lamontii, C. fargesii, C. eyrei and C. jucunda). Sixteen primer pairs showed successful amplification in all five Castanopsis species (80%), and the transferability ratios ranged from 90% to 100%. These developed EST-SSR markers can be applied to population genetic and germplasm evaluations of C. carlesii and related species.